Effectiveness of Colored Stick In Improving Addition Skills for Deaf Children - Cahaya Sha'adah Aiyouti; Zulmiyetri Zulmiyetri; Mega Iswari; Setia Budi (Universitas Muhammadiyah Enrekang, 2024)
This research aims to investigate the effectiveness of colored sticks in improving lateral addition skills, with sums ranging from more than 10 to 20, among sixth-grade deaf students at SLB Hikmah Reformasi Padang. The research employs an SSR approach with an A-B-A design. It consists of 13 sessions divided into three phases. The first phase, baseline (A1), spans 3 meetings, showing stable results with a score of 20. The second phase, intervention (B), lasts for 7 meetings, indicating improvement with scores increasing from 30 to 75 and demonstrating stability from the 9th to the 10th meeting. The final phase, another baseline (A2), takes place over 3 meetings, showing stable results with a score of 90 in the 12th and 13th meetings. These findings indicate an enhancement in addition skills, with results up to 20, using colored sticks among deaf children.